2012
DOI: 10.1038/eye.2012.256
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication in eye cancer: the latest tumor, node, metastasis classification and beyond

Abstract: The tumour, node, metastasis (TNM) classification is a universal cancer staging system, which has been used for five decades. The current seventh edition became effective in 2010 and covers six ophthalmic sites: eyelids, conjunctiva, uvea, retina, orbit, and lacrimal gland; and five cancer types: carcinoma, sarcoma, melanoma, retinoblastoma, and lymphoma. The TNM categories are based on the anatomic extent of the primary tumour (T), regional lymph node metastases (N), and systemic metastases (M). The T categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 54 publications
2
44
0
5
Order By: Relevance
“…Ophthalmic radiation may be used as a curative therapy, as adjuvant treatment following surgical excision, or as palliative therapy for advanced cases of eyelid and conjunctival tumors (18) . Some reports have mentioned that radiation therapy has not proved useful and generally results in the loss of the eye as a complication (17)(18)(19) . However, in our experience and in the experience of others (18)(19)(20) , the use of adjuvant therapy is being increased due the greater prevalence of limited (organ preservative) resections, with little, but useful, increase in survival and local control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ophthalmic radiation may be used as a curative therapy, as adjuvant treatment following surgical excision, or as palliative therapy for advanced cases of eyelid and conjunctival tumors (18) . Some reports have mentioned that radiation therapy has not proved useful and generally results in the loss of the eye as a complication (17)(18)(19) . However, in our experience and in the experience of others (18)(19)(20) , the use of adjuvant therapy is being increased due the greater prevalence of limited (organ preservative) resections, with little, but useful, increase in survival and local control.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review set a survival rate at 5 and 10 years of ~85% and 70%, respectively (17) . Overall mortality reported in different studies is ~25% (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Local spread of tumor cells into the neighboring tissues occurs through the invasion of the choroid or postlaminar invasion of the optic nerve. 36 Although relatively rare, retinoblastoma also metastasizes to distant sites via the lymphatic system, and several clinical factors have been identified that predict the likelihood of retinoblastoma recurrence and metastasis. For example, secondary neovascular glaucoma is highly predictive of optic nerve invasion.…”
Section: Expression Of the Neural Stem Cell Marker Sox2mentioning
confidence: 99%
“…Posterior uveal melanoma, together with metastatic carcinoma, is the most common primary intraocular malignant tumor in adults [1]. Standardized incidence rates of uveal melanoma in Europe (from 1983 to 1994) increased from south to north, from minimum of <2 per million in registries of Spain and southern Italy, up to >8 per million in Norway and Denmark [2].…”
Section: Introductionmentioning
confidence: 99%
“…Iris melanomas have the best and ciliary body melanomas have the worst prognosis. Tumor size and optic nerve infiltration are the best parameters used to predict the survival and metastatic potential of the tumor [1,3,8,10]. Histopathologically choroidal melanoma has a spectrum of cell types, ranging from thin and plump spindle cells to epithelioid cells (spindle-cell, mixedcell, and epithelioid-cell types) [5].…”
Section: Introductionmentioning
confidence: 99%